(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
A cross-sectional study was conducted in Al-Hilla City, Babylon Province, Iraq, of 300 women who gave birth via Cesarean section at the two main maternity surgical wards in the city from a period from 1st of December 2017 to 15th of March, 2018. The mothers came from mixed urban and rural backgrounds. Socio-demographic and obstetric data were recorded. Neonatal data were extracted from the medical records of the labor and neonatal care wards. The study included mothers of all ages, one fifth (23%) of whom were teenagers and minors marrying at a very young age (31%). Unfortunately (64%) had poor or negative attitudes to breastfeeding. Lack of motivation and self-confidence are also major reasons for very early cessation of breastfeeding. This study cited that the Cesarean section per se is a major cause of quitting natural feeding. The patients were influenced by advice from not only close relatives but also doctors and health personnel after the Caesarean section.